STEM Workers, H-1B Visas, and Productivity in US Cities - Peri, Giovanni; Shih, Kevin; Sparber, Chad (Journal of Labor Economics, 2015)
Science, technology, engineering, and mathematics (STEM) workers are fundamental inputs for innovation, the main driver of productivity growth. We identify the long-run effect of STEM employment growth on outcomes for native workers across 219 US cities from 1990 to 2010. We use the 1980 distribution of foreign-born STEM workers and variation in the H-1B visa program to identify supply-driven STEM increases across cities. Increases in STEM workers are associated with significant wage gains for college-educated natives. Gains for non-college-educated natives are smaller but still significant. Our results imply that foreign STEM increased total factor productivity growth in US cities.